Kesesuaian Strategi dan Lingkungan: Telaah dari Perspektif Deterministik-Pilihan Strategik - Pinasti, Margani; Mulia, Teodora Winda (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2007)
The aim of this paper is to discuss fit strategy-environmental, in different perspective. Environment looked into from perspective of strategic deterministic-strategic choices, becoming organizational theory area focus. Pursuant to perspective of deterministic -strategic choices, can be identified four quadrant (Hrebiniak and Joyce model, 1985) environment type faced by company, that is (1) high determinism, low choice (Quadrant I); ( 2) high determinism, high choice (quadrant II); (3) low determinism, high choice (quadrant III) ( d) low determinism, low choice (quadrant IV). Every quadrant chime in with the type and process the different ,,trot